2018
DOI: 10.1186/s40981-018-0215-9
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic considerations for cesarean section in a parturient complicated by Scimitar syndrome-like pathophysiology

Abstract: Background: Pre-existing poor respiratory function is a significant challenge for women to successfully continue pregnancy and accomplish delivery. Case: Pregnancy and delivery were successfully managed without any maternal or neonatal complications, in a 26year-old woman with severely impaired respiratory function, due to a unilateral hypoplastic lung, accompanying Scimitar syndrome-like circulation. Hyperventilation, normally observed even at the first trimester, was absent by the end of the second trimester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…We also included the case that is published in this paper, for a total of 14 studies. 4 8 9 10 11 12 13 14 15 16 17 18 19…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also included the case that is published in this paper, for a total of 14 studies. 4 8 9 10 11 12 13 14 15 16 17 18 19…”
Section: Resultsmentioning
confidence: 99%
“…We identified 14 studies describing UAPA impacting 22 pregnancies. 4,[8][9][10][11][12][13][14][15][16][17][18][19] The median age at diagnosis in our study was 21 years versus a median age of 14 years reported in studies not restricted to pregnant patients. 3 This may reflect selection, where those with more severe symptoms facilitating earlier diagnosis are less likely to pursue pregnancy.…”
Section: Main Findingsmentioning
confidence: 99%